Geometric morphometric analysis of blue swimming crab, portunus pelagicus in Hagonoy, Bulacan. - Villa, Charmaine Marie. 4 0 16; 5 (2005)
ABSTRACT: This paper examined Blue swimming crab, Portunus pelagicus, in Hagonoy, Bulacan, through geometric and morphometric analysis. Shape variations and allometry in sizes of the samples taken from a fishpond and directly from seawater were compared. Samples were preserved in 10% formalin and were authenticated. Measurements of seven different crab parts were taken manually Pictures were taken utilizing a digital camera and landmarking on the images was done through software. on the images was done through software. Results indicate that there are shape variations among the samples studied in relation to the differences in their gender, right and left claw size and the environment where they were taken. There is also a degree of allometry observed on the observed on the seven different parts of crabs measured.
Thesis:(B.S. Biology)- Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2